The Impact of Unclear Limits on Press Freedom on Legal Uncertainty and Efforts to Strengthen Regulations to Realize Professional and Accountable Journalism - Sofhuan Yusfiansyah; Subianta Mandala (PT. ALHAFI BERKAH INDONESIA, 2025)
This study focuses on the importance of regulating restrictions on press freedom in the dissemination of information in Indonesia to analyze the related legal aspects and identify the impacts that arise due to the unclear regulation. Based on a normative legal study with a statute approach, the main findings obtained indicate that until now, Law Number 40 of 1999 concerning the Press has not specifically regulated the limitations of press freedom, which leads to the potential for abuse of this freedom, such as the spread of hoaxes, slander, or inaccurate information that can harm various parties, both individuals, groups, and the state. It risks weakening the quality of journalism because the media tends to prioritize sensation over accuracy and truth. Therefore, this study emphasizes the urgency of revising and improving existing regulations so that press freedom remains a pillar of democracy, but within clear limits and by legal principles and journalistic ethics, to prevent potential abuse that can damage reputation and social stability.